THE USE OF STORYTELLING TECHNIQUES IN ENGLISH LANGUAGE TEACHING (Web of Teachers: Inderscience Research, 2025)
This article analyzes the effectiveness of using storytelling for teaching English in classes. The article also reveals the importance of the storytelling method and several effective reasons to use it in English lessons. The main purpose of the article is to identify the advantages of the method through storytelling in developing the students' speech activity, expanding the vocabulary and shaping the skills of communication.